Experimental and molecular genetic analysis of the impact of pyrethroid and non-pyrethroid insecticide impregnated bednets for mosquito control in an area of pyrethroid resistance. - Kolaczinski, J; Fanello, C; Hervé, J; Conway, D; Carnevale, P; Curtis, C (2000)
Experimental huts in Côte d'Ivoire were used to evaluate the pyrethroid alpha-cypermethrin, the non-ester pyrethroid etofenprox, the organophosphate pirimiphos-methyl and the carbamate carbosulfan on bednets against pyrethroid-resistant Anopheles gambiae Giles. To test for selection for the resistance gene by the treated nets, A. gambiae collected live or dead from the huts were kept and analysed for the presence of the kdr gene using a new polymerase chain reaction followed by sequence-specific oligonucleotide probing (PCR-SSOP) for kdr-genotyping. Deliberately holed bednets freshly treated with pirimiphos-methyl or carbosulfan caused over 90% kill of A. gambiae s.s. and Culex spp. However, the mortality with alpha-cypermethrin or etofenprox treated nets was similar to that with untreated nets. Bloodfeeding of A. gambiae s.s. on the sleepers under the nets was only significantly reduced by alpha-cypermethrin and carbosulfan. Tests of the residual activity of the bednets after seven months showed that pirimiphos-methyl had lost its efficacy while carbosulfan still performed well. Once again the pyrethroid treated nets gave similar results to the untreated nets. Selection for the kdr-allele by alpha-cypermethrin and etofenprox, but not by carbosulfan, was indicated by PCR-SSOP genotyping of mosquitoes. Thus carbamates such as carbosulfan, or organophosphates of longer persistence than pirimiphos-methyl and of low mammalian toxicity, would seem to be a promising alternative to be used on bednets, particularly in areas of pyrethroid resistance.